Cost-effectiveness of national mandatory screening of all admissions to English National Health Service hospitals for meticillin-resistant Staphylococcus aureus: a mathematical modelling study. Issue 3 (March 2016) - Robotham, Julie V; Deeny, Sarah R; Fuller, Chris; Hopkins, Susan; Cookson, Barry; Stone, Sheldon
Summary: Background: In December, 2010, National Health Service (NHS) England introduced national mandatory screening of all admissions for meticillin-resistant Staphylococcus aureus (MRSA). We aimed to assess the effectiveness and cost-effectiveness of this policy, from a regional or national health-care decision makers' perspective, compared with alternative screening strategies. Methods: We used an individual-based dynamic transmission model parameterised with national MRSA audit data to assess the effectiveness and cost-effectiveness of admission screening of patients in English NHS hospitals compared with five alternative strategies (including no screening, checklist-activated screening, and high-risk specialty-based screening), accompanied by patient isolation and decolonisation, over a 5 year time horizon. We evaluated strategies for different NHS hospital types (acute, teaching, and specialist), MRSA prevalence, and transmission potentials using probabilistic sensitivity analyses. Findings: Compared with no screening, mean cost per quality-adjusted life-year (QALY) of screening all admissions was £89 000–148 000 (range £68 000–222 000), and this strategy was consistently more costly and less effective than alternatives for all hospital types. At a £30 000/QALY willingness-to-pay threshold and current prevalence, only the no-screening strategy was cost effective. The next best strategies were, in acute and teaching hospitals, targeting of high-risk specialty admissions (30–40% chance of cost-effectiveness; mean incremental cost-effectiveness ratios [ICERs] £45 200 [range £35 300–61 400] and £48 000/QALY [£34 600–74 800], respectively) and, in specialist hospitals, screening these patients plus risk-factor-based screening of low-risk specialties (a roughly 20% chance of cost-effectiveness; mean ICER £62 600/QALY [£48 000–89 400]). As prevalence and transmission increased, targeting of high-risk specialties became the optimum strategy at the NHS willingness-to-pay threshold (£30 000/QALY). Switching from screening all admissions to only high-risk specialty admissions resulted in a mean reduction in total costs per year (not considering uncertainty) of £2·7 million per acute hospital, £2·9 million per teaching, and £474 000 per specialist hospital for a minimum rise in infections (about one infection per year per hospital). Interpretation: Our results show that screening all admissions for MRSA is unlikely to be cost effective in England at the current NHS willingness-to-pay threshold, and our findings informed modified guidance to NHS England in 2014. Screening admissions to high-risk specialties is likely to represent better resource use in terms of cost per QALY gained. Funding: UK Department of Health.